Demotic Accounts: Some Notes on the Form and Content - Eid, Eid Nagy.
This essay aims at shedding some light on Demotic accounts as a vital administrative tool in the ancient Egyptian’s everyday life in the Late and Greco-Roman Periods as evidenced by the large number of published accounts. Account documents belong to Demotic documentary texts and they usually record lists of various amounts of specific items that have been paid or received by certain individuals in different transactions. Such documents began to be recorded in Demotic from the Twenty-Sixth Dynasty. Among the abundant vocabulary of accounts in Demotic, ip  “account” and wn  “list” seem to be the only two words which were used to refer to accounts as a type of text. A full-structured account, which is not the case in most of Demotic accounts, normally contains a maximum number of three elements, that is, the heading, the main body, and the closing formula.